HUBUNGAN MINAT DAN POTENSI DIRI DENGAN PEMILIHAN PROGRAM STUDI ASURANSI SYARIAH MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SUMATERA UTARA - Muhammad Arif (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to determine the relationship of variables of interest, self-potential, with the decision of students to choose the study program of Takaful insurance. The research method used is quantitative research method with primary data obtained from the questionnaire data measured using Likers scale. The data of this study were collected by using questionnaires which were then processed by using multiple linear regression test with the help of SPSS 17 program. The result of this study stated that the interest variable (X1) correlated positively and significantly to the selection of sharia study program with a partial correlation of 0.358 with p <0 , 05., self-potential variable (X2) correlated positively and significantly to the selection of sharia study program with partial correlation of 0408 with p <0,05, while together with the variable of interest and self potential also positive influence toward the selection of Sharia insurance program evidenced by the coefficient of Frag = 58.654 where p <0.05.